Piketty meets Pasinetti: On public investment and intelligent machinery - Linus Mattauch; David Klenert; Joseph E. Stiglitz; Ottmar Edenhofer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
N/A
Keywords: D31; E21; H31; H41; H54; 330